Cephalotaxine-type and homoerythrina-type alkaloids with antiproliferative effects from Cephalotaxus fortunei. Issue 35 (25th August 2022) - Zhao, Chun-Xue; Liu, Hui; Zhang, Xin; Yang, Meng-Yue; Wang, Yue-Tong; Xing, Yi-Jia; Hua, Jun-Xin; Zhang, Qin; Li, Da-Hong; Bai, Jiao; Jing, Yong-Kui; Hua, Hui-Ming
Abstract : 1 is the first nitrogen-oxidized homoerythrina-type alkaloid isolated from Cephalotaxus genus. 31 exhibited a significant antitumor effect in THP-1 and K562 cancer cell lines with GI50 values of 0.24 and 0.29 μM. Abstract : Twenty-two cephalotaxine-type and ten homoerythrina-type alkaloids, including seven previously undescribed ones, were isolated from the twigs and leaves and the seed kernels of Cephalotaxus fortunei . Their structures were established by spectroscopic analysis, single crystal X-ray diffraction, and ECD calculation methods. Cephalofortunine A β- N -oxide (1 ) is the first nitrogen-oxidized homoerythrina-type alkaloid. The isolated compounds were evaluated for their in vitro antiproliferative effects against two human leukemia cell lines (THP-1 and K562). All compounds showed different levels of antiproliferation in THP-1 and K562 cells with GI50 values of 0.24–29.55 μM. Hainanensine (31 ) was the most active against two cancer cell lines with GI50 values of 0.24 ± 0.07, and 0.29 ± 0.01 μM, respectively.